2008
DOI: 10.1007/s11136-008-9399-1
|View full text |Cite
|
Sign up to set email alerts
|

Lower visual acuity predicts worse utility values among patients with type 2 diabetes

Abstract: This study aimed to estimate disutility associated with visual loss in patients with diabetes using a community-based sample and controlled for many characteristics associated with quality of life. We found a smaller utility decrement compared to other studies, suggesting that visual acuity's impact on the quality of life for patients with diabetes in the community setting differs from more selected populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
2
28
1
1
Order By: Relevance
“…Smith et al [31] fitted a linear regression and found visual angle to be a predictor of EQ-5D utility values. They also fitted a nonparametric ordinal logistic regression and this estimated that any degree of visual impairment would see an increased likelihood of reporting nonperfect utility values.…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al [31] fitted a linear regression and found visual angle to be a predictor of EQ-5D utility values. They also fitted a nonparametric ordinal logistic regression and this estimated that any degree of visual impairment would see an increased likelihood of reporting nonperfect utility values.…”
Section: Resultsmentioning
confidence: 99%
“…Mean DR preferences were generally higher than other studies, decreasing incrementally from 0.98 to 0.67, most probably due to methodological differences 47. Data for multi-attribute utilities are scarce, with only two studies using the EQ-5D 49 50. Critically, for all utility measures, the values tended to systematically decrease with worsening levels of visual acuity of DR severity.…”
Section: Impact Of Dr On Prosmentioning
confidence: 72%
“…In a retrospective study within the Kaiser Permanente Northwest health care system, Smith et al 13 extracted best corrected VA from 2074 free text notes using a computer program written in Python programming language. They validated their results by manual chart review of 100 notes, but no details about the algorithm logic or results of the validation were reported.…”
Section: Discussionmentioning
confidence: 99%